A review of land settlements in the Philippines 1900-1975 - Paderanga, Cayetano W., Jr (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1987)
The history of land settlement programs in the Philippines from 1900 to 1975 is reviewed from secondary sources, including three case studies. A few similarities are noticed among all of the resettlement movements.